Differences in biomarker testing in non-small cell lung cancer: real-world outcomes within an integrated healthcare system - Carroway, William P.; Alcasid, Nathan J.; Jarrin Lopez, Alberto; Williams, Kenneth; Sarovar, Varada; Dong, Huyun; Dyer, Wendy; Yang, Jingrong; Sakoda, Lori C.; Velotta, Jeffrey B. (Frontiers in Surgery, 2025)
IntroductionWhile biomarker testing can guide lung cancer treatment, its real-world application in community practice remains underexplored. This study examines the prevalence, predictors, and outcomes of biomarker testing in non-small cell lung cancer (NSCLC).MethodsThis retrospective cohort study included adults diagnosed with primary NSCLC from 2013 to 2020 within a large integrated healthcare system. We linked cancer registry and electronic health records to determine the prevalence of biomarker testing, including single-gene, multi-gene, and next-generation sequencing (NGS), overall and stratified by patient characteristics including age, gender, race/ethnicity, smoking status, and stage. Multivariable regression analyses were conducted to identify independent predictors of biomarker testing and evaluate associations between type of biomarker testing and 3-year all-cause mortality, overall and stratified by stage.ResultsAmong 8,267 NSCLC patients, 38.9% received biomarker testing. Testing prevalence increased with disease stage: I (6.9%), II (18.0%), III (34.8%), IV (71.1%). Testing was more prevalent in patients aged <65 years, of Asian race, and who never smoked, lived in less deprived neighborhoods, and had non-squamous tumors. Younger age, never smoking, Asian race, and stage IV disease were independent predictors of biomarker testing. NGS vs. no testing was associated with 13% decreases in 3-year all-cause mortality.ConclusionsBiomarker testing prevalence was higher in advanced stage NSCLC as expected, with decreased 3-year mortality in patients who received NGS testing. Our findings in a large real-world diverse population suggest that broader uptake of comprehensive biomarker testing across all stages of NSCLC is warranted for improved outcomes.